(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2025)
The coverage of babies receiving exclusive breastfeeding in Indonesia is 61.33%, and based on the results of a survey in Serangan Village, there were 9 (11.5%) families who did not provide exclusive breastfeeding on the grounds that breast milk did not come out, the mother was busy and the child did not want to breastfeed. The purpose of this study was to identify the provision of exclusive breastfeeding to mothers that was carried out according to standards. Method: Data collection in this case study was carried out by conducting interviews, documentation studies and observations. Results: After being given Health Education and care such as oxytocin massage, mothers hoped to be able to breastfeed their babies again and mothers would use birth control and take their babies to get immunizations. Conclusion: The care provided focused on efforts to increase breast milk production through a holistic approach.